Judicial role in globalised economy with a focus on tax treaties - Jha, Shiva Kant (New Delhi, 2005)
The book examines, in the context of the realities of a globalized world with Market supremacy, the role of the superior courts and the reach and ambit of Art 32 of the Constitution of India.
Keywords: Economy-India-Judicial role